Prudentius and the landscapes of late antiquity - O'Hogan, Cillian (Oxford University Press, 2016)
This work considers the representation of the geographical and cultural landscapes of late antiquity in the work of the Latin poet Prudentius. It argues that his use of allusion to Augustan and early imperial Latin authors presents these landscapes as being marked by the arrival of Christianity, though retaining the grandeur of the pagan past